INVESTIGATING THE IMPACT OF SOILS’ PHYSICOCHEMICAL COMPOSITION ON CHLORSULFURON PEDOSPHERIC SORPTION - AHMAD, Khuram Shahzad (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Chlorsulfuron (1-(2-chlorophenyl) sulfonyl-3-(4-methoxy-6-methyl-1, 3, 5- triazin-2-yl)), a Sulfonyl herbicide was investigated for its sorption behaviour in soils from various geographical locations. The results, fitting Freundlich and Linear equations, depicted a C type curve. Linear distribution coefficient value (Kd) spanned in a range of 8.2-23.0 µg/ml while Freundlich distribution coefficient value (Kf) was found to be 7.06 -17.41 µg/ml. Low Gibbs free energy values (-14.9 to -16.0 kJ/mol) are indicative of physisorption process. The regression and correlation analysis depicted pH to be negatively correlated (r=-0.936) while organic matter and organic carbon to be positively correlated with Kd (r=0.989 and r=0.988 respectively). However, the soil texture rendered positive correlation with clay (r=0.897) and negative correlation with sand and silt (r=-0.990 and r=-0.820 respectively). Desorption hysteresis coefficient (H), in all four soil was found to be less than 1 (0.44 to 0.62). Results have been statistically evaluated by ANOVA and the accuracy of fit has been calculated by plotting residual graphs in Minitab. This study is a milestone for further investigation based on Chlorsulfuron degradation and mobility patterns.